永磁传动技术的发展现状和展望 - 杨超君; 顾红伟 (Jixie chuandong)
Along with the development of science and technology, the permanent magnetic drive technology is developed step by step. It has formed various drive structures up to now. The structure, theory and characteristics of the some usual permanent magnetic drive with the examples are introduced. The research background and operating principle of magnetic couplings are emphasize introduced. Especially the resisting high temperature asynchronous magnetic couplings developed by Joint Institute of Jiangsu University and XuShiFen （HongKong） which effectively resolved the problem that the magnets on internal rotors of synchronous magnetic couplings are demagnetized under the high temperature term. Because it operated by electromagnetic induction principle without magnet in its internal rotor. Some usual design and calculation methods of permanent magnetic drive is also introduced. At last brought forward the problem of magnetic drive is brought forward and the prospect of magnetic drive is carried out.